2001
DOI: 10.1346/ccmn.2001.0490202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Montmorillonite Surfaces After Modification by Organosilane

Abstract: Abstract--X-ray powder diffraction (XRD), thermal gravimetric analysis (TGA), surface area measurements, and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy were used to examine the surface properties of organosilane-modified smectite-type aluminosilicate clays. Organic modified clays derived from the reactions of montmorillonite (containing 93-95% montmorillonite from a bentonite, <1% quartz, and 4-6% opal CT) with octadecyltrichlorosilane (C~sH37SiCI3) and octadecyltrimethoxysilane [CIsH37Si(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 41 publications
5
78
0
2
Order By: Relevance
“…Natural and activated clay were considered fast because of a rapid increase of adsorbates adsorbed were occurred at the 180 min. Previous findings on the adsorption of phenolic compounds by various clay-based adsorbents have shown a wide range of adsorption time (Song and Sandi 2001).…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…Natural and activated clay were considered fast because of a rapid increase of adsorbates adsorbed were occurred at the 180 min. Previous findings on the adsorption of phenolic compounds by various clay-based adsorbents have shown a wide range of adsorption time (Song and Sandi 2001).…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…Adsorption of intercalant (organo-cations) on clay caused a constriction of the pore channels owing to attachment of the intercalant moieties to the internal framework surfaces. Moreover, organic intercalant coated the outer surface of the nanoclay make it inaccessible to nitrogen molecules (Song and Sandí, 2001). This can lead to a substantial decrease in the SSA of OC compared to that of the pristine clay (Krishna et al, 2000).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The basal spacing of the silylated products strongly depended on the configuration of the silane used [17], the loaded silane amount in the interlayer spaces [18] and the interactions among silane molecules (e.g., intermolecular hydrogen bonding) and between clay mineral and special group of silane (e.g., -NH 2 group) [20]. The chemical nature of the solvents used in silylation reaction has significant influences on the amount and distribution of the grafted silanes and the structure of the silylated products [16,21,22]. Shanmugharaj et al reported that the surface energy of the solvents showed a significant effect on the average basal spacing of the grafted products [16].…”
Section: Introductionmentioning
confidence: 99%